2018
DOI: 10.1063/1.5041801
|View full text |Cite
|
Sign up to set email alerts
|

Boundary interface condition of magnetic fluid determines the magnetic levitation force experienced by a permanent magnet suspended in the magnetic fluid

Abstract: The buoyancy experienced by a permanent magnet suspended in magnetic fluid is studied, and the expression for calculating the magnetic fluid buoyancy is derived. The magnetic fluid buoyancy or magnetic fluid levitation force, which can be obtained by calculating the sum of Archimedes levitation force and magnetic levitation force, depends on the boundary interface condition of magnetic fluid. The type of the boundary interface and the pressure over it determine the boundary interface condition, and the depende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…The choice of damping factor or damper in practical systems depends on the system's practical applications. Several dampers such as ferrofluid damper, viscous damper, viscoelastic damper, friction damper, eddy current damper and metallic damper were reported by various researchers such as Yu et al [60], Zhou et al [61], Constantinou et al [62], Ye et al [63], Jiao et al [64], Tsai et al [65], Javanmardi et al [66], etc Yang [67] suggested two different types of ferrofluid dampers that might be applied to reduce rotating machine vibration. The ferrofluid being studied has a better damping effectiveness, making it more effective going forward for suppressing system vibration [68], controlling vibratory motion like noise [69], and mechanical oscillation by dissipating energy [70,71].…”
Section: Damping Factor Analysismentioning
confidence: 99%
“…The choice of damping factor or damper in practical systems depends on the system's practical applications. Several dampers such as ferrofluid damper, viscous damper, viscoelastic damper, friction damper, eddy current damper and metallic damper were reported by various researchers such as Yu et al [60], Zhou et al [61], Constantinou et al [62], Ye et al [63], Jiao et al [64], Tsai et al [65], Javanmardi et al [66], etc Yang [67] suggested two different types of ferrofluid dampers that might be applied to reduce rotating machine vibration. The ferrofluid being studied has a better damping effectiveness, making it more effective going forward for suppressing system vibration [68], controlling vibratory motion like noise [69], and mechanical oscillation by dissipating energy [70,71].…”
Section: Damping Factor Analysismentioning
confidence: 99%
“…Equation 4 [76] can be used to calculate the levitation force of any magnetic or non-magnetic object immersed in a ferrofluid under a magnetic field:…”
Section: Levitation Characteristicsmentioning
confidence: 99%
“…Pocket bearings on the other hand rely on both the pressurised air pocket, which is encapsulated by the ferrofluid seal, and the pressure inside the seal itself. The pressure is a result of the magnetic body force which depends on the external magnetic field and the boundary condition of the magnetic fluid [32,33].…”
Section: Introductionmentioning
confidence: 99%